Edukasi Hukum Penggunaan AI bagi Siswa SMK N 1 Kaligondang: Mensinergikan Kreativitas dan Integritas Akademik - Pujangga Candrawijayaning Fajri; Hesti Ayu Wahyuni (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The use of AI in today’s era has significantly expanded across various sectors of life, including the education sector. The use of AI in education is quite helpful in improving the quality of learning by providing innovative teaching materials, real-time feedback, and fostering student creativity; however, in practice, there are numerous instances of misuse of AI, such as for criminal activities. Such practices are clearly counterproductive to the learning process and threaten the quality of the nation’s future generations. The objective of this community service initiative is to deepen students’ understanding of AI from a legal perspective and to enhance the quality of learning. The methods employed include participatory-based education, encompassing lectures, Q&A sessions, and statements of commitment. The results of this community service initiative include an enhanced understanding of AI and its proper use. Additionally, students have committed to using AI ethically, in accordance with existing legal frameworks, and with a focus on improving the quality of learning without compromising their foundational and social skills, so that in the future they can compete effectively both nationally and internationally.